Synthesis of Mannich Eugenol Oxirane Morpholine compound as antifungal in vitro and in silico (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The use of antifungal drugs increases along with the increase in fungal infections. This causes the fungus to be resistant to antifungal drugs, one of which is the azole class of drugs. This increase resistance poses a major threat to global health services. This research aims to synthesize eugenol-morpholine compound reacted with epichlorohydrin as antifungal drug in vitro and in silico. In silico testing uses the molecular docking method with the discovery studio application. Synthesis of eugenol-morpholine and synthesis of eugenol oxirane morpholine using the reflux method. Characterization of synthetic compounds using NMR. The synthesized compound was applied for in vitro testing on the Candida albicans fungus using the disc diffusion method. The results of in vitro and in silico research show that the compound eugenol oxirane morpholine has better antifungal activity compared to the compounds eugenol-morpholine and eugenol. The results of in silico research showed a cDOCKER value of -38.5537 kcal/mol and the in vitro results had an inhibition zone of 28.55 mm. The best compound as an antifungal drug candidate is the compound eugenol oxirane morpholine with the lowest cDOCKER value in in silico testing and a wide zone of inhibition in in vitro testing showing very strong activity.
Keywords: Candida albicans; docking; epiklorohydrin; eugenol; reflux